Carbon footprint and energy used in mega underwater reinforced concrete structure - Phua, Yee Hwee. (2012)
With Singapore’s increasing population, a demand of land space for housing development raises. Several of methods like building HDB flats higher, were being looked into for better use of the land space we have. One of the methods proposed was to build a mega underwater structure.